2020
DOI: 10.1039/d0cp00136h
|View full text |Cite
|
Sign up to set email alerts
|

Temperature- and pressure-dependent kinetics of the competing C–O bond fission reactions of dimethoxymethane

Abstract: Under typical shock tube conditions, dimethoxymethane decomposes mainly to give CH3 + OCH2OCH3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…The assumption that the rates of the unimolecular C–O decomposition can be taken as for DME and DEE is therefore somewhat acceptable in the low-temperature range. However, as a dedicated work on the unimolecular bond scission reactions of OME 1 , the calculated rate constants by Golka et al are expected to be more accurate as it matches the experimentally measured rate constants at lower pressures.…”
Section: Recommendations For Model Developmentmentioning
confidence: 88%
See 4 more Smart Citations
“…The assumption that the rates of the unimolecular C–O decomposition can be taken as for DME and DEE is therefore somewhat acceptable in the low-temperature range. However, as a dedicated work on the unimolecular bond scission reactions of OME 1 , the calculated rate constants by Golka et al are expected to be more accurate as it matches the experimentally measured rate constants at lower pressures.…”
Section: Recommendations For Model Developmentmentioning
confidence: 88%
“…The roaming reaction (R7) has been shown to be sensitive on reactivity only at elevated temperatures. , The kinetic parameters found in literature vary by several orders of magnitude, as illustrated in Figure . Note that, in their experimental work, Golka et al indicated that no molecular channel was found.…”
Section: Recommendations For Model Developmentmentioning
confidence: 96%
See 3 more Smart Citations